Analisis Faktor-Faktor Yang Menentukan Disiplin Kerja Karyawan Pada PT. BPR Luhur Damai Tabanan - Putra Bangsawan, I Gst Ngr Bagus (E-Jurnal Manajemen; Vol 2 No 1 (2013), 2013)
Labor discipline is an employee attitudes and behaviors embodied in the willingness of an employee with full consciousness and sincerity sincerity or with no compulsion to comply with and implement all company regulations and policies in carrying out the duties and responsibilities in an effort to contribute the maximum in the achievement of corporate goals . This study aims to determine the factors that determine employees' discipline PT. BPR Luhur Damai Tabanan using the 20 variables and the population in this study were all employees of PT. BPR Luhur Damai Tabanan. Using factor analysis techniques, gained 4 that determine employees' discipline PT. BPR Luhur Damai Tabanan. These four factors are the factors of education and training, disciplinary factors, leadership factors and salaries, and compensation factors. While the variables representing each of the factors that determine employees' discipline PT. BPR Luhur Damai Tabanan is variable and career opportunities, variable attendance, variable boss firmness, and variable office allowances. Keywords: Factor analysis, employee discipline